2002
DOI: 10.1002/1099-0682(200207)2002:7<1772::aid-ejic1772>3.0.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Peralkylated Four- and Five-Membered Cyclosilanes Containing a Heteroatom: Synthesis, Structure, and Properties

Abstract: Seventeen peralkylated four-and five-membered heteroatom-containing silacycles [R 1 R 2 Si] n X [R 1 = iPr and/or R 2 = tBuCH 2 ; n = 3; X = CH 2 (1a, 1b), NR 3 (R 3 = C 6 H 11 ) (3a−d), O (5a−c), and n = 4; X = CH 2 (2a, 2b), NR 3 (R 3 = C 6 H 11 or Pr) (4a−d), and O (6a, 6b)] have been synthesized and characterized. The structural features of twelve compounds − 1b, 3a−d, and 5b (Si 3 X) and 2a, 4a−c, 6a, and 6b (Si 4 X) − determined by X-ray analysis have been investigated and geometrical differences between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
2
2
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…30,31 In particular, the influence of nitrogen substituents is underexplored. 32,33 Here, we investigate how nitrogen couples σand πconjugated fragments in N-aryl substituted cyclosilazanes. Synthetic and X-ray crystallographic studies are reported.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…30,31 In particular, the influence of nitrogen substituents is underexplored. 32,33 Here, we investigate how nitrogen couples σand πconjugated fragments in N-aryl substituted cyclosilazanes. Synthetic and X-ray crystallographic studies are reported.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The relationship between SiN heterocycle structure and electronic properties is poorly understood, as studies of cyclic SiN compounds (silazanes) have focused on their use as precursors to polysilazanes by ring-opening polymerization and silicon nitride ceramics by pyrolysis. , In particular, the influence of nitrogen substituents is underexplored. , …”
Section: Introductionmentioning
confidence: 99%